Cardiovascular proteomics in the era of big data: experimental and computational advances. Issue 1 (December 2016) - Lam, Maggie; Lau, Edward; Ng, Dominic; Wang, Ding; Ping, Peipei
Abstract Proteomics plays an increasingly important role in our quest to understand cardiovascular biology. Fueled by analytical and computational advances in the past decade, proteomics applications can now go beyond merely inventorying protein species, and address sophisticated questions on cardiac physiology. The advent of massive mass spectrometry datasets has in turn led to increasing intersection between proteomics and big data science. Here we review new frontiers in technological developments and their applications to cardiovascular medicine. The impact of big data science on cardiovascular proteomics investigations and translation to medicine is highlighted.